Antioxidant, antibacterial activity and FICI (Fractional Inhibitory Concentration Index) of ethanolic extract of Melastoma malabathricum leaves with amoxicillin against pathogenic bacteria - PRATIWI APRIDAMAYANTI; Rafika Sari; Anita Rachmaningtyas; Vella Aranthi (Nusantara Bioscience, 2021)
Abstract. Apridamayanti P, Sari R, Rachmaningtyas A, Aranthi V. 2021. Antioxidant, antibacterial activity, and FICI (Fractional Inhibitory Concentration Index) of ethanolic extract of Melastoma malabathricum leaves with amoxicillin against pathogenic bacteria. Nusantara Bioscience 13: 140-147. Cengkodok plants (Melastoma malabathricum L.) from the Melastomataceae tribe have properties as a fever reliever (antipyretic), pain reliever (analgesic), relieve swelling, and treat burns or bleeding wounds. This study aimed to determine the antioxidant activity, total phenol content, total flavonoids, and MIC value of ethanol extract of M. malabathricum leaves against Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Proteus mirabilis, and Pseudomonas aeruginosa. The method used in this study was the antioxidant activity was carried out using the DPPH test, the total phenol-flavonoid content by using gallic-quercetin acid comparison and measurement with Spectrophotometry UV/Vis. Antibacterial activity was carried out by the Kirby-Bauer disc diffusion method. Antioxidant activity in this study showed IC50 value = 5.28µg/mL. The chemical constituent's total phenols are 36.645 ± 5.14%, and the total flavonoids are 4.163 ± 0.2%. Antibacterial activity MIC values ??were obtained at a concentration of 6.25 mg/mL against B. cereus with a diameter of 8.28 mm ± 0.225, against B. subtilis with a diameter of 8.53 mm ± 0.275, against S. aureus with a diameter of 7.23 mm ± 0.275, against S. epidermidis with a diameter of 6.18 mm ± 0.104; MIC values ??obtained at a concentration of 1.56 mg/mL in E. coli with a diameter of inhibition zone 6.77 ± 0.72 mm, P. mirabilis with a diameter of inhibition zone 6.32 ± 0.19 mm, and P. aeruginosa with a diameter of inhibition zone 6.40 ± 0.26 mm. The characteristic of the combination of cengkodok leaf ethanol extract and Amoxicillin towards S. epidermidis and B. subtilis with FICI value is one categories additive; P. aeruginosa with FICI value is two categories indifferent; E. coli, B. cereus, S. aureus, and P. mirabilis with FICI value is 0.5 categories synergistic.